STRES KERJA, KINERJA DAN PERAN MEDIASI MOTIVASI KERJA - Lestari, Ni Kadek Indah Dian; Manuati Dewi, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.01.TAHUN.2023DO - 10.24843/EEB.2023.v12.i01.p04, 2023)
Employee performance is an important aspect in the company because it can affect the company's overall performance. This study aims to analyze the role of work motivation in mediating the effect of job stress on employee performance. The research location is the Regional Public Company for Drinking Water Tirta Sewakadarma Denpasar City. The population is all employees, totaling 303 people. The sample used was 178 respondents who were calculated by the Slovin formula and determined by the proportional random sampling method. Data collection methods in this study used interviews and questionnaires. The hypothesis was tested by Path Analysis and Sobel Test. The results showed that work stress has a negative and significant effect on employee performance, work motivation has a positive and significant effect on employee performance, work stress has a negative and significant effect on work motivation, and work motivation acts as a mediator of the effect of work stress on employee performance. Theoretically, the results of this study provide support for Expectancy Theory. Practically, the results of this study are expected to be a reference for the Perumda Water Drinking Tirta Sewakadarma Denpasar City in order to improve the performance of its employees